Sustainable Materials for Contemporary Architecture: A Review - Davies O.O.A.; Davies I.E.E; Davies R.M (International Journal of Rural and Regional Development, 2024)
The sustainability materials in the construction industry are crucial for fostering a more effective economy marked by reduced energy, waste, and pollution, lower emissions, improved safety of residents in public and residents through boosting interior air quality, increased job opportunities, and a more equitable wealth distribution. The objective of this study is to conduct an in-depth examination of sustainable construction materials by analyzing the challenges, barriers, prospects, motivations, and choices related to perceptions from different stakeholders. The evaluation procedure consisted of examining documents that were published in three reputable scientific databases, which included review articles, conference proceedings, and journal papers. This study presents an extensive examination of the most recent advancements, limitations, and future possibilities of more than forty sustainable construction materials. It was found that the selection of building materials considers their physical, chemical, and mechanical characteristics, as well as the financial capabilities of the clients. It was also asserted that the utilization of sustainable materials depends on their functional, technical, and climatic considerations, as well as the natural disaster vulnerabilities unique to the area. Various challenges and opportunities related to sustainable construction materials, such as technical, economic, and sociocultural barriers, were recognized. It is crucial to underscore the active participation of governments, industry, academia, and interdisciplinary collaborations in promoting and implementing sustainable materials. The outcome of this research offers a valuable point of reference for different stakeholders, such as professionals, government officials, clients, policymakers, scholars, and individuals responsible for making decisions, and proposes recommendations based on the relevant previous research
Keywords: Bamboo; construction industry; green building; greenhouse gases; sustainable materials